Novel method for the generation of tissue-engineered vascular grafts based on a highly compacted fibrin matrix. (1st January 2016) - Aper, Thomas; Wilhelmi, Mathias; Gebhardt, Christin; Hoeffler, Klaus; Benecke, Nils; Hilfiker, Andres; Haverich, Axel
Graphical abstract: Abstract: The generation of tissue-engineered blood vessel substitutes remains an ongoing challenge for cardiovascular tissue engineering. Full biocompatibility and immediate availability have emerged as central issues for clinical use. To address these issues, we developed a technique that allows the generation of highly stable tubular fibrin segments. The process is based on the compaction of fibrin in a custom-made high-speed rotation mold. In an automated process, fibrin is precipitated from plasma by means of the Vivostat® system. Following application to the rotating mold, the fibrin was compacted by centrifugal force and excess fluid was pressed out. This compaction results in increasing cross-links between the fibrin fibrils and a corresponding significant increase of biomechanical stability up to a burst strength of 230 mm of mercury. The molding process allows for a simultaneous seeding procedure. In a first in vivo evaluation in a sheep model, segments of the carotid artery were replaced by tissue-engineered vascular grafts, generated immediately prior to implantation ( n = 6). Following subjection to the body's remodeling mechanisms, the segments showed a high structural similarity to a native artery after explantation at 6 months. Thus, this technique may represent a powerful tool for the generation of biomechanically stable vascular grafts immediately prior to implantation. Statement of significance: Fibrin has previously been shown to be suitable as a matrix for the seeding of different celltypes and for that reason was widely used as scaffold in different fields of tissue engineering. Nevertheless, fibrin's lack of stability has strongly limited its application. Our study describes a novel moulding technique for the generation of a highly compacted fibrin matrix. Using this approach, it was possible to optimize the engineering process of tubular fibrin segments to provide bioartificial vascular grafts within one hour with sufficient stability for immediate implantation in the arterial system. Thus, this technique may represent a powerful tool to get closer to the ultimate aim of an optimal bioartificial vascular graft.